2004
DOI: 10.1073/pnas.0406403101
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein gene (PRNP) variants and evidence for strong purifying selection in functionally important regions of bovine exon 3

Abstract: Amino acid replacements encoded by the prion protein gene (PRNP) have been associated with transmissible and hereditary spongiform encephalopathies in mammalian species. However, an association between bovine spongiform encephalopathy (BSE) and bovine PRNP exon 3 has not been detected. Moreover, little is currently known regarding the mechanisms of evolution influencing the bovine PRNP gene. Therefore, in this study we evaluated the patterns of nucleotide variation associated with PRNP exon 3 for 36 breeds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 60 publications
3
52
0
Order By: Relevance
“…This indicates that 'loss of function' of bovine PrP C itself does not cause BSE and that ablation of the normal cellular prion protein PrP C function does not adversely affect normal bovine development. It has been reported that evolution has exerted very intense purifying selection on exon 3 of bovine PRNP; the PRNP gene should have some indispensable function in bovine development because such strong purifying selection is usually seen only for proteins essential to eukaryotic life 21 . Therefore, our findings appear to be of particular interest in supporting a general hypothesis that PrP C function is dispensable for normal animal development.…”
mentioning
confidence: 99%
“…This indicates that 'loss of function' of bovine PrP C itself does not cause BSE and that ablation of the normal cellular prion protein PrP C function does not adversely affect normal bovine development. It has been reported that evolution has exerted very intense purifying selection on exon 3 of bovine PRNP; the PRNP gene should have some indispensable function in bovine development because such strong purifying selection is usually seen only for proteins essential to eukaryotic life 21 . Therefore, our findings appear to be of particular interest in supporting a general hypothesis that PrP C function is dispensable for normal animal development.…”
mentioning
confidence: 99%
“…Generally, the bovine with the low PrP expression level has an advantage on resistance to BSE, and increasing the frequencies of 12-bp insertion and 23-bp insertion alleles will be improving the resistance to BSE (Sander et al 2005;Xue et al 2008). Furthermore, it was reported that an increased number of octapeptide repeats in bovine PRNP would enhance host susceptibility to BSE, and the general number of repeats was five or six in previous reports (Castilla et al 2005;Brun et al 2007), and the number of it had four and/or seven in a few cattle (Sander et al 2004;Seabury et al 2004). These advances on PRNP polymorphisms provided theory guidance for cattle genetics and breeding.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of some intermediate-frequency polymorphisms remains interesting and warrants a wider resequencing study and examination of the effect of the polymorphisms on protein structure and function. Another study (Seabury et al 2004) evaluated genetic variation in the exon 3 of PRNP in 36 breeds of domestic cattle and other bovine species and found negative selection against nonsynonymous changes and an excess of rare silent polymorphisms upstream the N-terminal cleavage site coding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary analyses of PRNP have demonstrated conflicting results, with the prion gene being under balancing (Mead et al 2003), purifying (Seabury et al 2004), and positive selection (Premzl and Gamulin 2009) depending on the dataset. A recent study including representatives of multiple taxa suggested that positive selection was acting on PrP in various domains and intradomains (Premzl and Gamulin 2009).…”
mentioning
confidence: 99%